Education Supervision and The Challenges Faced by Supervisors in Implementing Their Responsibilities in Tanzania - Mbawala, Julius Jonas; Hermanto, Hermanto (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2023)
Education supervision is the process of professional development of the teacher, primarily by giving the teacher feedback about classroom interactions and helping the teacher make sure the feedback is used to improve the teacher's behavior to make teaching and learning more effective. Quality education results from effective and efficient supervision of education whereby a supervisor creates a conducive environment for teachers to perform their responsibilities. The paper intends to explore the role and challenges facing education supervisors in doing their responsibilities in Tanzania. To achieve this, the researchers did a mini-review. The paper searched the internet for relevant and timely research papers and articles mainly focusing on supervision in secondary schools. Once a sufficient number of materials for the mini-review had been gathered, the laborious process of assessing and analyzing the concepts and contexts within each piece commenced. The study finds that the quality of education depends on the presence of a competent and committed school headmaster in supervising the critical effectiveness of the school, while challenges facing education supervisors are categorized into two categories: Problems in instruction supervision and administrative supervision. In solving these problems, education supervision has to be put into consideration by the government as it plays a vital role in improving educational performance.